Implementation of Electric Vehicle Policy in DKI Jakarta to Realize Environmentally Friendly Mobility - Ziddane Rafian Ziddane; Tati Tati (JURNAL ECONOMINA, 2026)
This study analyzes the implementation of electric vehicle policy in Jakarta Province using George C. Edward III's policy implementation theory and the Environmental, Social, and Governance (ESG) approach. A qualitative descriptive method was employed through interviews, observation, and document analysis. The findings indicate that policy implementation has not been fully effective. Major challenges include limited public awareness, uneven charging infrastructure, high vehicle prices, and insufficient institutional capacity. Although the government has demonstrated commitment through regulations and incentives, public adoption remains limited. Strengthening communication, expanding infrastructure, and ensuring policy consistency are essential to improve the effectiveness and sustainability of electric vehicle policy implementation.